ARMING OR CHARMING: OBSEQUIUM AND DOMESTIC POLITICS IN ROMAN NORTH AFRICA - De Marre, M.E.A. (Akroterion, 2012)
Scholarship to date has dealt mainly with the legal aspects of Roman marriage and its place within Roman society, most of which tends to focus on the disempowerment of women. This article, while not denying the disadvantages women suffered under these conditions, focusses on the mechanics by which women could achieve their aims within the boundaries of marriage and how the concept of obsequium could have been understood and implemented by both partners to the marriage contract.